Analysis of the role of village-owned enterprises (BUMDes) in improving the economy of the community in sharia-based Patokan village - Suryana, Ahmad; Thompson, Emily; Marliana, Marliana (AL-MUQARANAH, 2024)
This research aims to analyze the role of Village-Owned Enterprises (BUMDes) in improving the economy of the Patokan Village community with a sharia-based approach. BUMDes is an economic institution established in villages to manage local potential and improve community welfare. In the context of Patokan Village, the application of sharia principles in BUMDes management is important given that the majority of the population is Muslim. This research uses a descriptive qualitative method, with data collection techniques in the form of in-depth interviews, observation, and documentation. The results showed that the BUMDes of Patokan Village has contributed positively to the village economy, especially through the savings and loan, livestock, and agriculture business units. However, there are still some obstacles, such as a lack of capital, skills, and community participation. The application of sharia in BUMDes management also provides additional benefits, such as increased community trust and avoidance of usury. This research is expected to provide theoretical and practical contributions in the development of a sharia-based BUMDes management model, which is more effective in supporting the welfare of village communities.